2022
DOI: 10.14218/jcth.2021.00425
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated Exosomes Are Involved in Hepatocellular Carcinoma Tumorigenesis, Diagnosis, and Treatment

Abstract: Hepatocellular carcinoma (HCC) has become a challenging disease worldwide. There are still limitations in the diagnosis and treatment of HCC, and its high metastatic capacity and high recurrence rate are the main reasons for its poor prognosis. The ability of extracellular vesicles (EVs) to transfer functionally-active substances and their widespread presence in almost all body fluids suggest their unprecedented potential in the study of various cancers. The unique physicochemical properties of EVs determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 112 publications
0
12
0
Order By: Relevance
“…Focusing on their functional role in HCC, it is reported that there is a great production of small extracellular vesicles (sEVs) (30–130 nm) from malignant hepatocytes, allowing cross-talk communication between HCC cells, in order to enhance cell proliferation, migration, and invasion, as well as metastatic dissemination [ 119 ]. There are several exosomal miRNAs that can be potentially isolated from serum, plasma, and urine, which can be utilized as diagnostic tools and prognostic or predictive biomarkers for HCC [ 120 , 121 , 122 , 123 , 124 ].…”
Section: The Interplay Between Evs and Mirnas In Hccmentioning
confidence: 99%
“…Focusing on their functional role in HCC, it is reported that there is a great production of small extracellular vesicles (sEVs) (30–130 nm) from malignant hepatocytes, allowing cross-talk communication between HCC cells, in order to enhance cell proliferation, migration, and invasion, as well as metastatic dissemination [ 119 ]. There are several exosomal miRNAs that can be potentially isolated from serum, plasma, and urine, which can be utilized as diagnostic tools and prognostic or predictive biomarkers for HCC [ 120 , 121 , 122 , 123 , 124 ].…”
Section: The Interplay Between Evs and Mirnas In Hccmentioning
confidence: 99%
“…Through autocrine and paracrine mechanisms, exosomes enable the interaction between tumor cells and TME, with immune-modulatory effects and the stimulation of the epithelial to mesenchymal transition that favors vascular invasion and metastatization [ 112 ]. Moreover, increasing evidence suggests that the interaction between tumor-derived exosomes, tumor cells, and TME may play a significant role in the development of drug resistance to TKIs in patients with HCC [ 113 , 114 , 115 , 116 , 117 , 118 ]. The exposure of PD-L1 on exosomes causes the direct inhibition of T cells’ function.…”
Section: Novel Biomarkersmentioning
confidence: 99%
“…In particular, ctDNA and CTCs have important prognostic implications, as they could identify mutational signatures that reflect the genomic landscape of the primary tumor [ 103 , 104 , 105 , 106 ]. In addition, exosomes, being able to modulate cellular communication directly and indirectly through the release of their cargos, provide important information on tumors’ mutational burden, invasiveness, and resistance during therapy to a degree surpassed by no other previous biomarker [ 112 , 113 , 114 , 115 , 116 ]. Compared with traditional AFP, it has been shown that ctDNA [ 81 , 82 , 83 ] might be a better prognostic marker of responses in patients with unresectable HCC, but these findings have not been confirmed in other studies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…EVs are produced by various immune cells, including B and T cells, macrophages, dendritic cells (DC), natural killer (NK) cells, mast cells, and thymocytes [ 164 , 214 , 215 , 216 , 217 , 218 ] and are rich in proteins with immune functions, such as antigen-presenting molecules (major histocompatibility complex (MHC) class I, MHC class II, CD1), adhesion molecules (CD11b, intercellular adhesion molecule 1 (ICAM-1)), and co-stimulatory proteins (CD86) [ 219 , 220 , 221 , 222 ]. Additionally, exosomes are involved in releasing intracellular components to the outside of cells as waste products, and through their loaded immune-related molecules, they have various immune functions, such as antigen presentation, including the priming of early T cells, differentiation of mature T cells, development of effector functions, and regulation of immune-related cells [ 223 , 224 , 225 , 226 , 227 ].…”
Section: Introductionmentioning
confidence: 99%